Coexistence of immunoglobulin G4-related kidney disease and acute hematogenous disseminated pulmonary tuberculosis: a case report - Zhou, Fangfang; Chu, Hanqing; Xu, Youjun; Zhang, Yena; Tan, Kuibi; Ge, Jinxia; Shao, Ningjun; Luo, Qun (Frontiers in Immunology, 2025)
BackgroundImmunoglobulin G4-related disease (IgG4-RD) is an immune-mediated fibrous inflammatory disease. Recently, an association between IgG4-RD and tuberculosis (TB) has been reported.Case summaryWe report a 56-year-old man complaining of a cough and poor appetite for 2 months and oliguria for 1 day. The patient was diagnosed with TB due to a manifestation of lymphatic TB and the radiological alterations of acute miliary pulmonary TB. He also presented with greatly elevated serum creatinine, non-albumin proteinuria, immunoglobulin subgroup IgG4, and immunoglobulin free light chain (FLC) levels. A diagnosis of IgG4-RKD was suggested by a renal biopsy. We then administered the patient glucocorticoid and anti-TB treatment for 4 months. The patient’s renal function was completely restored and the manifestations of TB were alleviated.ConclusionThe necessity and complexity of differential diagnosis in patients with coexisting IgG4-RD and TB remains challenging. Early recognition and timely treatment are important for averting its progression. Long-term monitoring is required to assess for recurrence of IgG4-RD and TB activity.